Classical Era Mongolian History Writing and a Review of Mongolian Sources - Kalan E. (Золотоордынское обозрение)
Abstract. Following their unification under Genghis Khan in 1206, the Mongols began an era in which they would play a very influential role in the course of history. Despite the existence of a negative perception of the Great Mongol Empire in the sources of the era, its impact on the political, economic, and cultural life of Eurasia has continued for generations. Although Mongolians adopted a writing system as late as 1204, the transfer of their oral tradition into writing lasted only a short time so that their historical heritage could be passed on to the next generations. The tradition of Mongolian historiography, which began with the creation of the stele known as the Genghis Stele, developed differently compared to other contemporary Asian states and it has kept this distinction until today. In addition to providing valuable information about the history of the Mongols and other nations they interacted with, historical sources written in Mongolian such as ‘Secret History of the Mongols’ and ‘Altan Tovch’ are also important milestones in Mongol historiography. Especially with works like ‘Altan Tovch’ and ‘Erdeniin Tovch’ being written during the period when Buddhism became widespread among the Mongols, the influence of Buddhist historiography on the Mongols became apparent. As a result, it is evident that grounds of legitimacy were strengthened in the actions of Mongol khans, especially Chinggis Khaan, and motifs indicating that divine power that was with these khans were added.